Neuromyelitis Optica Spectrum Disorder Attack Triggered by Herpes Zoster Infection. (25th April 2020) - Turco, Emanuela Claudia; Curti, Erica; Maffini, Valentina; Pisani, Francesco; Granella, Franco
Abstract : Neuromyelitis optica spectrum disorder is a severe autoimmune disease of the central nervous system characterized by recurrent inflammatory events primarily involving the optic nerves and spinal cord. Recently, a triggering role of infectious events in the development of NMOSD has been suggested. Varicella zoster virus is the most common viral infection involved, though the linkage with anti-aquaporin-4 antibodies is so far unknown. We report, to the best of our knowledge, the first pediatric case report about NMOSD relapse triggered by herpes zoster infection. The strict temporal relationship between VZV infection and NMO attacks seems to be more than simply due to chance; however, further reports are needed to be confirmed.